Workers level of understanding on Islam as a way of life and the concepts of worship (‘IBADAT’) to Allah - Rusli, Ahmad (2017)
This paper focuses on the study of higher learning institution workers (academician, professional and management group and supporting staff) levels of understanding about Islam as a way of life, the concepts of worship and their level of understanding on the attributes of work as worshiping (‘Ibadat’) Allah applies to their workplace. It is timely to study about this topic since not many study focuses on this important issue. Study on workers generally occurs in a more generic perspectives about their behavior and work place and work productivity. The study uses pragmatism research philosophy and in this study only quantitative data used which was collected through an online using google online questionaire tools of facilities. All muslim staff (1751) were invited to be involved in this study and around 179 useful questionnaires were used for further analyzed. It can be concluded that research findings show that the majority of respondents in this study admit or agree that Islam is a way of life. This means they are aware that the teachings and guidelines contained in Islam can be applied in their daily lives. Based on the findings of this study, clearly respondents have a positive perception of the concept of worship. They realize that worship is a major demand in their lives whether in the world or hereafter. They also realize that this concept of worship can be applied in all aspects of their life. They reject the worship only for things related to prayer, zakat and fasting only. The findings as a whole show that respondents follow all the principles set out to make their work in the category of worship to God. This is in line with the views given by Al-Qaradawy (2013) and the views of some other Islamic intellectuals. Implications and recommendations of the research findings were also discussed in this paper.